Strategi Pembiasaan Literasi Pagi Untuk Optimalisasi Pemahaman Belajar Siswa Sekolah Dasar: Penelitian - Muhammad Nisfatun Ni'am Mi'rajudin; Friska Nursukma; Khairal Mukhlisa; Intan Nur Rahmawati; Ahmad Rifqi; Beti Istanti Suwandayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The 15-minute morning literacy program in elementary schools often runs as an administrative routine that has little impact on improving students' in-depth learning comprehension. This study aims to analyze and map the most effective literacy habit-forming strategies to optimize students' cognitive abilities through a Systematic Literature Review (SLR) approach. Using the PRISMA guidelines with the Scopus database (2020–2025), this study examined articles that met the inclusion criteria. The results of the analysis show that the effectiveness of morning literacy can be improved through three main strategies: integrating gamification and technology to trigger intrinsic motivation, utilizing Open Education Resources (OER) in the pre-reading phase to activate prior knowledge, and strengthening the home literacy environment through active parental involvement. The synergy of these three elements has been proven to transform passive reading activities into meaningful interactive learning experiences. This study concludes that the transformation of school literacy strategies is absolutely necessary to support students' transition from learning to read to reading to learn in a sustainable manner.